CHANGES IN HOUSEHOLD AND GENERAL GOVERNMENT CONSUMPTION AND SAVINGS DURING THE COVID-19 PANDEMIC IN THE EUROPEAN UNION - Boris Crnković; Juraj Rašić; Sofija Turjak (Economic Review, 2022)
In March 2020, the COVID-19 pandemic caused a significant economic shock in countries worldwide, negatively affecting every aspect of the world economy. Due to the situation with the COVID-19 pandemic, governments imposed a lockdown on households to slow the spread of the pandemic. It was unknown how long the lockdown could last and how much impact it would have on households and the general government. Household consumption is a specific component of final GDP consumption and generally represents about 60% of GDP. Crises most often affect the individual and manifest in unplanned and unnecessary costs that affect household consumption and savings, and consequently growth and development. Eurostat states that the household savings rate of the European Union (EU) decreased in the third quarter of 2020 but was 4.5% higher than in 2019. This paper aims to analyze the differences in household consumption expenditure and net savings across the EU from 2018 until 2021 and general government consumption expenditure and net savings. In addition, it will compare the differences in household and general government consumption and savings in 2019 and 2020. This paper uses univariate statistical methods to define the differences between the EU member states and their private and public consumption expenditure and net savings. The authors will suggest further research on the topic mentioned above and provide evidence on how households should react to future pandemic situations.